2006
DOI: 10.1002/jmri.20593
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diffusion tensor imaging of the human calf muscle

Abstract: Purpose:To demonstrate the feasibility of in vivo calf muscle fiber tracking in human subjects. Materials and Methods:An EPI-based diffusion tensor imaging (DTI) sequence with six-direction diffusion gradient sensitization was implemented, and DT images were acquired at 3 Tesla on five subjects using an extremity coil. The mean diffusivity, fractional anisotropy (FA), and fiber angle (with respect to the magnet z-axis) were measured in different muscles, and fibers were tracked from several regions of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
136
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(154 citation statements)
references
References 32 publications
17
136
1
Order By: Relevance
“…Also, several studies have reported an ordered distribution of v 2 and v 3 within individual muscles [86-88]. However, a definitive structural basis for λ 2 / v 2 and λ 3 / v 3 has yet to be concluded.…”
Section: Diffusion-tensor Mri Of Skeletal Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Also, several studies have reported an ordered distribution of v 2 and v 3 within individual muscles [86-88]. However, a definitive structural basis for λ 2 / v 2 and λ 3 / v 3 has yet to be concluded.…”
Section: Diffusion-tensor Mri Of Skeletal Musclementioning
confidence: 99%
“…When imaging the lower leg, we use an MRI-compatible foot restraint/force measurement system to provide consistent, motion-limited positioning and control plantarflexion/dorsiflexion angle [97]. To achieve a similar result, Sinha et al [86] and Froeling et al [98] have described scaffold systems for the leg and forearm, respectively.…”
Section: Diffusion-tensor Mri Of Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the spinal cord [15][16][17] and calf muscles [18] have shown promising results for DTI. Ries et al [15] applied DTI to subjects suffering from a narrowing of the cervical canal and observed substantial differences in diffusion characteristics to detect lesions in the spine.…”
Section: Motivationmentioning
confidence: 99%
“…Ducreux et al [17] reconstructed 3D fiber tracts to visualize the deformation of the posterior spinal cord lemniscal and corticospinal tracts. Finally, Sinha et al [18] performed calf muscle fiber tracking in vivo using DTI in human subjects.…”
Section: Motivationmentioning
confidence: 99%